2019
DOI: 10.1080/09540261.2019.1682529
|View full text |Cite
|
Sign up to set email alerts
|

History of traumatic brain injury interferes with accurate diagnosis of Alzheimer’s dementia: a nation-wide case-control study

Abstract: Background: Traumatic brain injury (TBI) and Alzheimer's disease (AD) bear a complex relationship, potentially increasing risk of one another reciprocally. However, recent evidence suggests post-TBI dementia exists as a distinct neurodegenerative syndrome, confounding AD diagnostic accuracy in clinical settings. This investigation sought to evaluate TBI's impact on the accuracy of clinician-diagnosed AD using gold standard neuropathological criteria. Methods:In this preliminary analysis, data was acquired from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In addition, we were able to investigate the impact of head injury severity in the subset of hospitalized cases using standardized criteria 31 . It is also important to consider the impact of a head injury diagnosis on a dementia diagnosis 37 as well as the timing of dementia diagnosis after head injury diagnosis, as head injury‐related symptoms may be misdiagnosed as dementia, particularly in the time following the head injury. We addressed this by performing 1‐ and 2‐year wash‐out analyses in which associations were somewhat attenuated, but remained significant, which suggests that part of the association between head injury and dementia may be driven by dementia diagnoses occurring close to the time of head injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we were able to investigate the impact of head injury severity in the subset of hospitalized cases using standardized criteria 31 . It is also important to consider the impact of a head injury diagnosis on a dementia diagnosis 37 as well as the timing of dementia diagnosis after head injury diagnosis, as head injury‐related symptoms may be misdiagnosed as dementia, particularly in the time following the head injury. We addressed this by performing 1‐ and 2‐year wash‐out analyses in which associations were somewhat attenuated, but remained significant, which suggests that part of the association between head injury and dementia may be driven by dementia diagnoses occurring close to the time of head injury.…”
Section: Discussionmentioning
confidence: 99%
“…Center Uniform Data Set (NACC-UDS), showed that TBI history was associated with clinician misdiagnosis of Alzheimer's disease (increased false-positives evaluated using gold-standard autopsy neuropathology). 7 Despite extensive investigation into connections between (1) TBI and dementia or (2) NPS with cognitive decline in dementia, there is little research into the influence of TBI on NPS in the course of dementia development. NPS occurring after TBI are often transient; however, in a portion of the population, symptoms persist permanently and cause a significant decrease in quality of life, independent of associated dementia onset.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence further clarifies the molecular mechanisms underlying TBI that trigger amyloid precursor protein (APP) and Tau cleavage mediating AD pathology in animals (68). Additionally, the relationship of TBI and AD has shown to be quite complex and the presence of TBI leads to misdiagnoses of AD, interferes with treatment plans and makes research studies difficult to interpret (69). However, Pakistan lacks state-of-the-art diagnostic assessment of dementia and its risk factors, including neuroimaging of brain injury and aging that are extremely limited in Pakistan due to the inadequate infrastructure and limited training of clinicians (63).…”
Section: Discussionmentioning
confidence: 99%